Do Customers All Respond The Same? Generational Differences on Customer Orientation and Satisfaction. - Chelangat, Diane; Flaherty, Karen; Korir, Michael (Archives of Business Research, 2017)
Organisations have improved customer satisfaction by being customer oriented in all levels. At the firm level, organisations seek to develop customer oriented organization by generating market intelligence regarding the needs of the customer and disseminating the intelligence across departments that will lead to organization wide responsiveness to it. At an individual level, organisations seek to recruit and train employees to exhibit customer orientation behaviour. This study focuses on customer level of responsiveness to persuasion from customer oriented employees and also existence of different levels of satisfaction among three generational cohort groups (Baby Boomers, Generation X and Generation Y). This study found generational differences on responsiveness hence pointing towards managers to develop products addressing different generations.